A tuba solo na obra de Almeida Prado : propostas interpretativas para a Sonata para piano e tuba, Omulú = The tuba solo in the work of Almeida Prado: interpretative proposals for Sonata for piano and tuba, Omulú - Dias, Alberto Tavares, 1982- (2019)
Orientador: Paulo Adriano Ronqui